Implementing Liveworksheets in Teaching Reading Comprehension of Sixth-Grade Students in SD Negeri 1 Kerobokan - Mahesuari, Kadek Diah Tantri; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (English Education Department STKIP Agama Hindu Singaraja, 2024)
This study aimed to investigate the effectiveness of Liveworksheets as teaching media on students’ reading comprehension. This study was in the form of pre-experimental research and used one group pre-test post-test as the design. The population and sample were involved one group contain 35 students. Data collection was conducted using reading comprehension test which was formed as multiple-choice questions. The data was analysed with descriptive and inferential statistics analysis. The result of this study shows the implementation of Liveworksheets had a significant effect on students’ reading comprehension. It can be seen on the paired sample t-test which got p < 0.05. Moreover, the effect size got 1.388 which categorized into large size. It can be concluded that the implementation of Liveworksheets had a significant effect on students’ reading comprehension.